Analisis Kekerasan Simbolik dalam Novel A Thousand Splendid Suns karya Khaled Hosseini (Perspektif Pierre Bourdieu): Symbolic Violence Analysis in Novel A Thousand Splendid Suns by Khaled Hosseini (Pierre Bourdieu's Perspective) - Andi Nurul Amaliah (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This research studies about the symbolic violence experienced by the women characters in the novel entitled A Thousand Splendid Suns by Khaled Hosseini. The forms of symbolic violences are identified and analyzed by the sociological perspective of Pierre Bourdieu. Bourdieu proposes that language is the means to perpetuate and to transform the symbolic power. The doer has an authority to establish value, norms, and standards, to dictate, and to control the other agents’paradigm making the violences received as the normal and legitimate actions. The result of this research shows that the symbolic violence is identified in the family. The woman character named Mariam experiencing verbal abuse from her mother regarding the status and the traditional conception of woman’s position in the culture. Meanwhile this lead character is also forced to early marriage. In addition, another woman character, Laila is also passively accepted all forms of violences. Both women are treated discriminatively in society and family.